Muzyka rozrywkowa w Bydgoszczy w latach siedemdziesiątych. Próba charakterystyki (Kronika Bydgoska, 2014)
During the 1970s, the Bydgoszcz rock stage was greatly influenced by such bands as Led Zeppelin, Black Sabbath, and guitarist Jimmy Hendrix. Rock music was still very popular thus the negative attitude of the authorities to it weakened. Thanks to opening of new clubs, mainly student and company clubs in workplaces, young performers had an ability to give concerts. In company clubs, bands rehearsed and used professional equipment; student clubs had much worse equipment in this matter. Elementary and middle schools gave also opportunities for bands, which had taken advantage of their rooms and had taken part in artistic activities of the school. Musicians of varied provenance (rock, jazz) performed in bands playing in entertainment establishments and restaurants. In addition to Estrada Bydgoska, the Polish Jazz Association was established, which was a very active company organizing artistic programs for performers from all over Poland. The city was also an active participant of music events, organizing, among others, the festival “Days of Bydgoszcz.”